Improving Organization Effectiveness in Manufacturing Through Lean Initiatives in Configure-To-Order (CTO) Production of Efficient Customer Delivery - Leong, Khoo Teng; Hock, Oo Yu (2020)
Organizational effectiveness and operational efficiency have become significantly importance in the manufacturing industry. ‘Lean’ initiatives involve execution and evaluation, the former benchmarking Six Sigma is Define-Measure-Analyze-Improve-Control (DMAIC), and the latter involves three criteria of key performances indicators, viz., the lean principle assessment framework (internal), cost-related matters (external), and customer expectations. Both these processes are directed at improving manufacturing process to gain a potent momentum in mass customization: CTO production. The objective of this research is to explore how mass customization, specific to CTO production, can adopt ‘lean’ to improve manufacturing process performance levels for organizational effectiveness, thereby increasing business competitiveness, and focusing on the manufacturing process of CTO work efficiency-quality product delivery at the factory floor level. The case study approach is employed to investigate how the ‘lean’ approach can improve the CTO manufacturing process. This research contributes to knowledge in the area of production and operations management, in particular: (a) highlighting the importance of ‘organization and customer values’ through ‘lean’ improvements to its results; and (b) mapping performance measurement relationship which extends to the sustainability, commitment and shared configured-processes results of quality end-product delivery to satisfied customers.